(untitled) (Applied Biological Research, 2019)
The present study was conducted in the year 2018-19 at DBSKKV, Dapoli, Maharashtra (India) with aim to physico-chemically and biologically characterize the vermicomposts prepared from the residues obtained from different agroforestry sources. Eisenia foetida was used in vermicomposting. The residues of 14 easily available agroforestry plant species were collected and prepared in different randomized blocks. Among the various species evaluated, Megathyrsus maximus, Eluecine coracana, Themenda species, Setaria sphacelata, Gmelina arborea and Termenelia tomentosa proved significantly superior in yielding higher and enriched vermicompost. Maximum decomposition during partial decomposition study for 120 days was observed in cereal and grass species. The 20 released earthworms in each treatment showed a population of 876.5 and 646.5 in M. maximus and O. sativa residues. The maximum recovery of vermicompost was observed in Bridelia retusa, T. tomentosa, M. maximus and S. sphacelate. Significant improvements in colour and bulk density were noticed in cereal, grass and nutritious plantation species (T. tomentosa). Maximum improvement in some physicochemical characteristics [pH, EC, OC, available NPK, total NPK] and microbial activities [CO2 evolution and bacterial, actinomycete and fungal populations] were observed in easily decomposed and nutritious species (T. tomentosa, G. arborea). Significantly high dehydrogenase activity, soil microbial biomass carbon and nitrogen, total N, total C and C:N ratio were observed in M. maximus, E. coracana, G. arborea and T. tomentosa. These species are recommended for producing quality vermicompost and its production on the farmers field.